M1 Deutetrabenazine: update on first time use of SD-809 in huntington's disease (First-HD) and alternative for reducing chorea in huntington's disease (ARC-HD). (13th September 2016) - Testa, Claudia; ,
Abstract : Objective: Evaluate the efficacy, safety and tolerability of deutetrabenazine for chorea in Huntington's disease (HD). Background: Deutetrabenazine (SD-809) is a novel deuterium containing VMAT2 inhibitor. When deuterium, a naturally occurring form of hydrogen, is at specific sites, in this case CYP2D6 enzymatic targets on the tetrabenazine (TBZ) molecule, it prolongs active metabolite half-lives and reduces metabolic variability, without changing target pharmacology. Deutetrabenazine achieves comparable area under the curve (AUC) with lower total daily dose and dose frequency than TBZ. Methods: First-HD was a randomised, double-blind, placebo-controlled trial with 8 weeks of titration to adequate chorea control plus a 4-week maintenance. The ongoing open-label ARC-HD has 2 groups: First-HD participants now in a long-term safety study; and patients switched overnight from TBZ to an AUC-matched deutetrabenazine dose with optional dose adjustments after 1 week. Results: 90 subjects (45:45) enrolled in First-HD (44% female, mean age = 53.7). The total maximal chorea (TMC) score on deutetrabenazine improved by 2.5 points (21%) over placebo from baseline to end maintenance (p < 0.0001). Significantly improved secondary endpoints were patient and clinical global impressions of change (each p = 0.002) and SF-36 physical functioning scale (p = 0.03). The deutetrabenazine group had a mean BMI gain of 0.6 (0.2) kg/m 2, compared with a loss in the placebo group of 0.1 (P = 0.002). Mean deutetrabenazine daily dose at end treatment was ~40 mg. Three subjects terminated early, 2 on placebo. In First-HD, the most common AEs in all subjects were irritability (deutetrabenazine 6.7% vs. placebo 13.3%), somnolence (11.1% vs. 4.4%), dry mouth (8.9% vs. 6.7%) and dizziness (4.4% vs. 8.9%). Depression, anxiety, akathisia and parkinsonism were reported at same or lower rates for deutetrabenazine vs placebo. 36 HD patients (60% male, mean age 52.4) with adequately controlled chorea on stable TBZ doses for at least 8 weeks enrolled in ARC-HD. Mean TMC change from baseline was −0.8 at both week 1 and 4. The mean TBZ dose was 41 mg; mean deutetrabenazine dose weeks 1 and 4 was 20 mg and 29 mg. 21 patients at week 8 had an improvement of −1.9 (SE 0.8) in TMC, with mean deutetrabenazine dose 33 mg. Conclusions: Deutetrabenazine can effectively and safely reduce chorea in HD. Improved functional and quality of life measures suggest effective chorea treatment with good tolerability and twice-daily dosing can provide clinically meaningful benefit. HD patients can safely and rapidly convert from TBZ to open-label deutetrabenazine.